Fading and Shadowing in Wireless Systems - Shankar, P. Mohana; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book offers a comprehensive overview of fading and shadowing in wireless channels. A number of statistical models including simple, hybrid, compound and cascaded ones are presented along with a detailed discussion of diversity techniques employed to mitigate the effects of fading and shadowing. The effects of co-channel interference before and after the implementation of diversity are also analyzed. To facilitate easy understanding of the models and the analysis, the background on probability and random variables is presented with relevant derivations of densities of the sums, products, ratios as well as order statistics of random variables. The book also provides material on digital modems of interest in wireless systems. The updated edition expands the background materials on probability by offering sections on Laplace and Mellin transforms, parameter estimation, statistical testing and receiver operating characteristics. Newer models for fading, shadowing and shadowed fading are included along with the analysis of diversity combining algorithms. In addition, this edition contains a new chapter on Cognitive Radio. Based on the response from readers of the First Edition, detailed Matlab scripts used in the preparation of this edition are provided. Wherever necessary, Maple scripts used are also provided. • Covers detailed analysis of fading and shadowing as well as their mitigation that are critical to the improvement of reliable wireless communication capabilities; • Second edition provides additional background materials with sections on Laplace and Mellin transforms, parameter estimation (ML and MoM), statistical testing (chi square) and receiver operating characteristics - also offers newer models of fading and shadowing and a new chapter on cognitive radio; • New edition provides detailed Matlab and Maple scripts helpful to computational modeling and analysis of wireless systems adding a pedagogic component.
Overview -- Concepts of Probability and Statistics -- Modems for Wireless Communications -- Modeling of Fading and Shadowing -- Diversity Techniques -- Interference in Wireless Channels -- Cognitive Radio -- Index.
Keywords: Telecommunication; Coding theory; Information theory; Computer science -- Mathematics; Communications Engineering, Networks; Coding and Information Theory; Mathematical Applications in Computer Science